The Influence of Annealing Temperature and Soaking Time on the Ductility of SG 255 - Mahmud, Fryad J.; Abdulrahman, Kawan M.; Muhammed, Hawkar J.; Seed, Barzan A. H. (Kurdistan Journal of Applied Research, 2017)
This study deals with the effect of annealing temperature on the mechanical properties of SG 255 steel. Furthermore it aims to experimentally obtain better mechanical properties in particular ductility with lower annealing temperature and to minimize the cost of the manufacturing. The SG 255 steel is used in manufacturing of domestic LPG cylinder at Halala Company located in Sulaimanyah/Iraq. A number of samples were made according to ISO 6892, and then heat treated with different annealing temperature (850, 900 and 950 ºC). Moreover, the mentioned samples were broken by tensile machine to obtain the required mechanical properties, and to be compared with that of Halala factory. It was shown that higher elongation percentage 34.18%El with lower annealing temperature 900 ºC can be achieved and this leads to decrease the cost of manufacturing without degrading of cylinder’s quality.